Analisis Wacana Kritis Teun A. Van Dijk tentang Pidato Politik Prabowo Subianto dalam Debat Calon Presiden pada Pemilihan Presiden - Sulistiyowati, Sulistiyowati (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
General elections in Indonesia, especially presidential elections, are always an event where political discourse expressed by candidates greatly influences the social and political dynamics of society. Prabowo Subianto, as one of the presidential candidates who participated in the 2014, 2019, and 2024 elections, has been consistent in conveying the main issues that are relevant to the nation's problems. In this context, an analysis of the discourse constructed by Prabowo Subianto is important to understand how his political message is received and developed in society. The focus of this thesis research is 1) What is the form of Prabowo Subianto's political speech discourse in the presidential candidate debates in the 2014, 2019 and 2024 presidential elections? 2) What is the description of Prabowo Subianto's political speech discourse in the presidential candidate debates in the 2014, 2019 and 2024 presidential elections? 3) How to interpret Prabowo Subianto's political speech discourse using Teun A. Van Dijk's critical discourse analysis model in the presidential candidate debates in the 2014, 2019 and 2024 presidential elections? The objectives of this thesis research are 1) What is the form of Prabowo Subianto's political speech discourse in the presidential candidate debates in the 2014, 2019 and 2024 presidential elections; 2) What is the description of Prabowo Subianto's political speech discourse in the presidential candidate debates in the 2014, 2019 and 2024 presidential elections; 3) How to interpret Prabowo Subianto's political speech discourse using Teun A. Van Dijk's critical discourse analysis model in the presidential candidate debates in the 2014, 2019 and 2024 presidential elections. The results of the study show that the discourse analysis of Prabowo Subianto's political speeches in the presidential candidate debates in the 2014, 2019, and 2024 presidential elections shows significant evolution in themes, contexts, and social cognitions that influence public acceptance of the speech. The text of the speech reflects a response to the changing social and political context, while the social cognition of society influences how the speech is received and interpreted. In Teun A. Van Dijk's critical discourse analysis, text, context, and social cognition are interrelated and influence each other. The text of Prabowo Subianto's speech reflects a response to the changing social and political context, while the social cognition of society influences how the speech is received and interpreted